Caracterização tectono-sedimentar do Grupo Lagoa Feia (Eocretáceo) no Campo de Pampo, sudoeste da Bacia de Campos - Zanão Neto, Luiz [UNESP] (Universidade Estadual Paulista (Unesp), 2009)
The Lagoa Feia Group (Early Cretaceous) is widely distributed around the Campos Basin, forming deep prospects in the basin. It has two large coquinas platforms shellfish, and the lower deck constituent important reservoir in the southwestern of this basin, a producer of oil in the trend-Badejo-Linguado-Pampo. Due to the rising national energy demand is necessary to see the incorporation of technical knowledge and training of human resources in the knowledge of petroleum reservoirs. In this sense, the Pampo Field, as well as other fields of the trend, fall as interesting target area for study. Accumulations of hydrocarbons are partitioning structural - stratigraphic only for the three fields. They are mixed origin of traps, with influence of structural, stratigraphic and diagenetic. With the development of catchment areas of the latter condition has manifested itself in such a way to verify parts with nonproducing wells, which are observed in the intervals coquinas are closed, with reduced thickness and / or low quality porous. The understanding of these accumulations, by testing structural, stratigraphic and reservoir and the use of geological and geophysical techniques, will bring a better understanding of the portions relating to economic accumulation or subeconomic development of hydrocarbons in this region, contributing to the scientific knowledge of the Pampo Field.

O Grupo Lagoa Feia (Eocretáceo) apresenta ampla distribuição pela Bacia de Campos, constituindo prospectos profundos na bacia. Possui duas extensas plataformas de coquinas de bivalves, sendo a plataforma inferior constituinte de importante reservatório na porção sudoeste da bacia, produtora de óleo no trend Badejo-Linguado-Pampo, onde se insere o Campo de Pampo, que compreende a área estudada. Este campo, assim como os demais que compõem o trend, enquadra-se como interessante área alvo para estudos. Os campos encontram-se inseridos no mesmo contexto quanto às acumulações de hidrocarbonetos, apresentando compartimentação estrutural – estratigráfica única. Constituem trapa de origem mista, com influência de fatores estruturais, estratigráficos e diagenéticos. Com a evolução dos campos da bacia este último condicionante manifestou-se como responsável à ocorrência de porções com poços não produtores, onde são observados intervalos em que as coquinas encontram-se fechadas, com reduzida espessura e/ou baixa qualidade porosa. O entendimento do Grupo Lagoa Feia no Campo de Pampo, através de análises estruturais, estratigráficas e de reservatório e do uso de técnicas geológicas e geofísicas, traz uma melhor compreensão das porções referentes ao acúmulo econômico ou sub-econômico de hidrocarbonetos desta região, contribuindo para o conhecimento científico do campo.
Keywords: Petróleo - Geologia; Plataforma de coquinas; Perfis geofásicos; Campos basin; Pampo field Lagoa Feia group; Coquinas plataforms; Geophysical logs